Even darkness sings : from Auschwitz to Hiroshima : finding hope in the saddest places on Earth - Cook, Thomas H. (Pegasus Books, 2018)
Thomas Cook has always been drawn to dark places, for the powerful emotions they evoke and for what we can learn from them. These lessons are often unexpected and sometimes profoundly intimate, but they are never straightforward. With his wife and daughter, Cook travels across the globe in search of darkness<U+2015>from Lourdes to Ghana, from San Francisco to Verdun, from the monumental, mechanised horror of Auschwitz to the intimate personal grief of a shrine to dead infants in Kamukura, Japan. Along the way he reflects on what these sites may teach us, not only about human history, but about our own personal histories. During the course of a lifetime of traveling to some of earth's most tragic locals, from the leper colony on Molokai to ground zero at Hiroshima, he finds not only darkness, but a light that can illuminate the darkness within each of us. Written in vivid prose, this is at once a personal memoir of exploration (both external and internal) and a strangely heartening look at the radiance and optimism that may be found at the very heart of darkness.